Antislavery, elite men, and the "voice of the British nation:" c.1790–1860 - Morecroft, Eleanor (History compass, 2017)
In the late 18th and 19th centuries, antislavery and other humanitarian writers often defined their views as "the voice of the British nation". To be allied with this metaphorical "voice" vouchsafed moral authority to elite men whose position as "natural" rulers was, in an age of reform, being challenged. Touching upon issues across a 70-year period, with particular focus on the 1830s and 40s, this essay develops this theme through the examples of Charles, George, and William Napier: aristocratic military officers who spoke or wrote in support of antislavery and against the ill treatment of indigenous peoples in India, Australia, and South Africa. Their attitudes fed into their own senses of self, moral authority, class consciousness, and nationhood, as well as how their public selves would be represented by others. The history of antislavery provides a beneficial lens through which masculine ideals, and the use of reformism to reinforce elite men's power in nation and empire, can be better understood. This approach resonates with scholarship that has sought to integrate antislavery with broader metropolitan and colonial themes.